Mathematical models and immune cell biology - Molina-París, Carmen; Lythe, Grant 1966-.; SpringerLink (Online Service). (New York, NY Springer, 2011)
Mathematical immunology is in a period of rapid expansion and excitement. At recent meetings, a common language and research direction has emerged amongst a world-class group of scientists and mathematicians. Mathematical Models and Immune Cell Biology aims to communicate these new ideas to a wider audience. The reader will be exposed to a variety of tools and methods that go hand-in-hand with the immunological processes being modeled. This volume contains chapters, written by immunologists and mathematicians, on thymocytes, on T cell interactions, activation, proliferation and homeostasis, as well as on dendritic cells, B cells and germinal centers. Chapters are devoted to measurement and imaging methods and to HIV and viral infections.
Preface -- Thymocyte development -- A review of mathematical models for T cell receptor triggering and antigen discrimination -- Dynamic tuning of T cell receptor specificity by co-receptors and costimulation -- T cell activation and function: role of signal strength -- The cyton model for lymphocyte proliferation and differentiation -- Modeling itravital two-photon data of lymphocyte migration and interaction -- Modeling lymphocyte dynamics in vivo -- Continuous-time birth and death processes: diversity maintenance of naïve T cells in the periphery -- Multivariate competition processes: a model for two competing T cell clonotypes -- Stochastic modeling of T Cell homeostasis for two competing clonotypes via the master equation -- Dendritic cell migration in the intestinal tract -- Reassessing germinal center reaction concepts -- B cell strategies of Ag recognition in a stratified immune system -- Dynamics of Peripheral regulatory and effector T cells competing for antigen presenting cells -- Mathematical models of the role of IL-2 in the interactions between helper and regulstory CD4+ T cells -- A Physicist?s approach to immunology -- Timescales of the adaptive immune response -- Using mathematical models to explore the role of cytoxic T lymphocytes in HIV infection -- Viral immunity and persistence -- Index.
Electronic reproduction.
Keywords: Immunology -- Mathematical models; Immunology